Management of impacted and dilacerated maxillary central incisor using tractional force - Nausheer Ahmed; Bhakthi Halapanavar; V N Aravinda; S J Rajalakshmi (Wolters Kluwer Medknow Publications, 2020)
The prominent tooth location and root anomalies of impacted dilacerated incisors are a clinically challenging task for the orthodontist. The absence of anterior maxillary teeth has a significant impact on esthetics, speech, mastication, and psychosocial well-being in young patients. By nature of the vicinity, the impacted maxillary central incisors in children trigger a troubling condition for parents concerned with esthetics. The position, angulation, and direction of the patient's erupting tooth and crown and age are factors that hinder an impacted tooth's prognosis. Among these, the appropriate diagnosis of dilaceration is a crucial determinant of successful treatment. Decisions are made depending on the severity of dilacerations, whether the maxillary central incisor should be exposed and aligned or extracted and replaced by a prosthesis. The first treatment option always chosen to save the impacted maxillary central incisor is the exposure of the tooth surgically, followed by orthodontic traction forces. To prevent more complications, early intervention and detection of such cases are, therefore, most important. This case report elucidates the triumphant management in a 15-year-old female patient of a vertically impacted and dilacerated maxillary right central incisor positioned high in the vestibule, treated with a combined approach of surgical exposure and spontaneous orthodontic traction force.